2017
DOI: 10.1111/josh.12582
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain in the School Setting: The Teachers' Point of View

Abstract: BACKGROUND:The aims of this study were to (1) examine the reactions of teachers and student teachers to children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Our results are in concordance with those obtained in the studies conducted by Logan and Curran [23] and Solé et al [22], who showed that teachers often report some barriers that interfere in their helping the students to mitigate the negative impact of pain. For example, Logan and Curran [23], using a focus group methodology, examined school personnel's understanding of youth's chronic pain and identified some situations difficult to manage related to this situation.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in concordance with those obtained in the studies conducted by Logan and Curran [23] and Solé et al [22], who showed that teachers often report some barriers that interfere in their helping the students to mitigate the negative impact of pain. For example, Logan and Curran [23], using a focus group methodology, examined school personnel's understanding of youth's chronic pain and identified some situations difficult to manage related to this situation.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study provide new data regarding the educational needs and resources that would be of help to teachers with students with chronic pain in their classes. In addition, this research studied the resources that teachers can use to help students with chronic pain achieve their best potential, thus improving and expanding previous findings [22,23]. The participation of a diverse body of stakeholders in this consensus study increased the value of the results by bringing a wider perspective on the problem [28].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations